A Lie Is a Lie: The Ethics of Lying in Business Negotiations. Issue 4 (23rd October 2022) - Sherwood, Charles N. C.
Abstract : I argue that lying in business negotiations is pro tanto wrong and no less wrong than lying in other contexts. First, I assert that lying in general is pro tanto wrong. Then, I examine and refute five arguments to the effect that lying in a business context is less wrong than lying in other contexts. The common thought behind these arguments—based on consent, self-defence, the "greater good, " fiduciary duty, and practicality—is that the particular circumstances which are characteristic of business negotiations are such that the wrongness of lying is either mitigated or eliminated completely. I argue that all these "special exemption" arguments fail. I conclude that, in the absence of a credible argument to the contrary, the same moral constraints must apply to lying in business negotiations as apply to lying in other contexts. Furthermore, I show that for the negotiator, there are real practical benefits from not lying.